2023
DOI: 10.37745/ijbmr.2013/vol11n42546
|View full text |Cite
|
Sign up to set email alerts
|

Money Market Instruments and Price Stability in Nigeria: 1981 – 2021

Ebimobowei Appah,
Sekeme Felix Tebepah

Abstract: The study examined money market instruments and price stability in Nigeria. The study specific objectives include to investigate the relationship between treasury bills, treasury certificates, development loans stock, bankers’ acceptance, commercial papers and federal government of Nigeria bonds on consumer price index in Nigeria. The study adopted purposive sampling technique and the sample size consist time series data from 1981 to 2021. The study used secondary data obtained from Central Bank of Nigeria (CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Money market instruments also play a role in price stability in Nigeria. The study by Appah (2023) found that treasury certificates and development stocks have a positive and significant influence on the consumer price index, while treasury bills and commercial papers have a negative and insignificant impact (Appah, 2023). This indicates that certain money market instruments can affect price stability in Nigeria (Appah, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Money market instruments also play a role in price stability in Nigeria. The study by Appah (2023) found that treasury certificates and development stocks have a positive and significant influence on the consumer price index, while treasury bills and commercial papers have a negative and insignificant impact (Appah, 2023). This indicates that certain money market instruments can affect price stability in Nigeria (Appah, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The study by Appah (2023) found that treasury certificates and development stocks have a positive and significant influence on the consumer price index, while treasury bills and commercial papers have a negative and insignificant impact (Appah, 2023). This indicates that certain money market instruments can affect price stability in Nigeria (Appah, 2023). The study by (2023) found that oil price volatility has a positive impact on real GDP in the short run, but its effect in the long run is not significant (Sule-Iko & Nwoye, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation